2018
DOI: 10.2147/copd.s179048
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the GOLD 2017 and new 16 subgroups (1A–4D) classifications in predicting exacerbation and mortality in COPD patients

Abstract: Background and objectiveA multidimensional assessment of COPD was recommended by the Global Initiative for Chronic Obstructive Lung Disease (GOLD) in 2013 and revised in 2017. We examined the ability of the GOLD 2017 and the new 16 subgroup (1A–4D) classifications to predict clinical outcomes, including exacerbation and mortality, and compared them with the GOLD 2013 classifications.MethodsPatients with COPD were recruited from January 2006 to December 2017. The predictive abilities of grades 1–4 and groups A–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 22 publications
4
25
1
Order By: Relevance
“…11 Other studies have compared the GOLD 2017 with the previous GOLD classifications to predict COPD exacerbation. In contrast to our study, three studies 11,12,35 observed that the GOLD 2017 and the GOLD 2011 classifications predicted exacerbation similarly well. The discrepancies might be because these studies did not take exacerbations as time-to-event data when comparing the discrimination ability.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…11 Other studies have compared the GOLD 2017 with the previous GOLD classifications to predict COPD exacerbation. In contrast to our study, three studies 11,12,35 observed that the GOLD 2017 and the GOLD 2011 classifications predicted exacerbation similarly well. The discrepancies might be because these studies did not take exacerbations as time-to-event data when comparing the discrimination ability.…”
Section: Discussioncontrasting
confidence: 99%
“…4 Since the publication of the GOLD 2017 classification, the prognostic value of this classification has been debatable with less clear findings. [9][10][11][12] To our knowledge, only one study has compared all three GOLD classifications and found that the GOLD 2017 classification predicted respiratory and all-cause mortality similarly well as the GOLD 2007 and GOLD 2011 classifications. 9 No previous studies have investigated the risk of COPD hospitalization using the GOLD 2017 classification or compared their discrimination ability with the previous GOLD classifications to predict COPD hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Our study confirms that patients classified as GOLD A had the best survival, and patients with GOLD D had the higher mortality in both classifications [ 22 24 ]. Mortality of groups B and C in GOLD 2015 lay in between A and D groups and often overlapped.…”
Section: Discussionsupporting
confidence: 83%
“… 11 However, these may have limitations. For instance, inconsistent mortality risk stratification for GOLD A-B-C-D, 17 weak prediction of AECOPD risk for DOSE, 18 and a need for further validation in longitudinal cohort studies and randomized controlled trials for SCOPEX. 11 Furthermore, risk scoring systems designed for the general population with COPD may not be appropriate in patients with high CV risk, considering that CV risk factors and CVD are associated with comparatively poorer respiratory and CV outcomes.…”
Section: Discussionmentioning
confidence: 99%